ЗОНАЛЬНО-СЕКТОРИАЛЬНЫЕ КРИСТАЛЛЫ ПИРИТА-ВАЭСИТА ИЗ ГИДРОТЕРМАЛИТОВ В СЕРПЕНТИНИТАХ ЗАПАДНОГО АМАНБУЛАКА (ТУРКМЕНИЯ) - Попов В.А.; Попова В.И.; Власова И.В.; Недосекова И.Л.; Нишанбаев Т.П. (My University, 2006)
There are characterized compositions of pyrite, millerite, bravoitc, vaesite, gcrsdorfite, polydymite and sphalerite. Zonal-sectorial crystals of pyrite-vaesite have overgrown upon needle-shaped millerite. Octahedral zones of the pyritc-vaesite crystals are composed only of vaesite (51 %al Ni), whereas their cube zones - of vaesite and pyrite (4 %„, Ni) rhythmically alternate with each other. Subsequently those crystals were overgrown by oriented gersdorfite.
Keywords: 549.324.3